Effect of abutment screw surface treatment on reliability of implant-supported crowns - Anchieta, Rodolfo Bruniera [UNESP]; Machado, Lucas Silveira [UNESP]; Bonfante, Estevam Augusto; Hirata, Ronaldo; Freitas, Amilcar Chagas; Coelho, Paulo G. (Quintessence Publishing, 2014)
Purpose: To evaluate and compare the reliability of implant-supported single crownsabutments retained with coated (C) or noncoated (NC) screws and onto platform-switched abutments with coated screws. Materials and Methods: Fifty-four implants (DT Implant 4-mm Standard Platform, Intra-Lock International) were divided into three groups (n = 18 each) as follows: matching-platform abutments secured with noncoated abutment screws (MNC); matching-platform abutments tightened with coated abutment screws (MC); and switched-platform abutments secured with coated abutment screws (SC). Screws were characterized by scanning electron microscopy and x-ray photoelectron spectroscopy (XPS). The specimens were subjected to step-stress accelerated life testing. Use-level probability Weibull curves and reliability for 100, 000 cycles at 200 N and 300 N (90%two-sided confidence intervals) were calculated. Polarized light and scanning electron microscopes were used for fractographic analysis. Results: Scanning electron microscopy revealed differences in surface texture; noncoated screws presented the typical machining grooves texture, whereas coated screws presented a plastically deformed surface layer. XPS revealed the same base components for both screws, with the exception of higher degrees of silicon in the SiO2 form for the coated samples. For 100, 000 cycles at 300 N, reliability values were 0.06 (0.01 to 0.16), 0.25 (0.09 to 0.45), and 0.25 (0.08 to 0.45), for MNC, MC, and SC, respectively. The most common failure mechanism for MNC was fracture of the abutment screw, followed by bending, or its fracture, along with fracture of the abutment or implant. Coated abutment screws most commonly fractured along with the abutment, irrespective of abutment type. Conclusion: Reliability was higher for both groups with the coated screw than with the uncoated screw. Failure modes differed between coated and uncoated groups.
Keywords: Abutment screw; Biomechanics; Dental implants; Reliability; Weibull curves